Prospective Comparison of Plasma Biomarker and Traditional Risk Factor Profiles for Incident Isolated Atherosclerotic Disease and Incident Isolated Abdominal Aortic Aneurysm - Acosta, Stefan; Fatemi, Shahab; Melander, Olle; Engström, Gunnar; Gottsäter, Anders (Frontiers in Cardiovascular Medicine, 2022)
Background Traditional risk factors for atherosclerotic disease (AD) are well known, of which some are relevant also for abdominal aortic aneurysm (AAA). The present study compares the importance of plasma biomarker and traditional risk factor profiles for incident AD without concomitant AAA (isolated AD) and AAA without concomitant AD (isolated AAA) during long-term follow-up. Methods In the Malmö Diet and Cancer Study - cardiovascular cohort, 5,381 participants free from atrial fibrillation or flutter, AD (coronary artery disease, atherothrombotic ischemic stroke, carotid artery disease or peripheral artery disease), and AAA underwent blood sampling under standardized fasting conditions between 1991 and 1994. Cox proportional hazards regression analysis was used to calculate hazard ratios (HR) with 95% confidence intervals (CI). Results During a median follow up of 23.1 years, 1152 participants developed isolated AD and 44 developed isolated AAA. Adjusted HR for lipoprotein-associated phospholipase A2 (mass) (HR 1.53, 95% CI 1.14–2.04 versus HR 1.05, 95% CI 0.99–1.12) was higher for incident isolated AAA compared to incident isolated AD, respectively. Mid-regional proadrenomedullin (MR-proADM) was associated with incident isolated AD (HR 1.17, 95% CI 1.10–1.25) and incident isolated AAA (HR 1.47, 95% CI 1.15–1.88). MR-proADM was correlated (r=0.32; p<0.001) to body mass index (BMI), and BMI was associated with increased risk of incident isolated AAA (HR 1.43, 95% CI 1.02–2.00). No participant with diabetes mellitus (DM) at baseline developed isolated AAA (0/44), whereas DM was associated with increased risk of isolated AD (HR 2.57, 95% CI 2.08–3.18). Adjusted HR for male sex (HR 4.80, 95% CI 2.42–9.48, versus HR 1.76, 95% CI 1.56–1.98) and current smoking (HR 4.79, 95% CI 2.42–9.47 versus HR 1.97, 95% CI 1.73–2.23) were higher in the incident isolated AAA group compared to the incident isolated AD group, respectively. Conclusions Data supports the view that components of vascular inflammation and cardiovascular stress drives AAA development, whereas glycated cross-links in abdominal aortic wall tissue may have a plausible role in reducing AAA risk in individuals with DM.